Das Ende eines Experiments : Umbruch in der DDR und deutsche Einheit - Reißig, Rolf 1941- Hrsg; Glaeßner, Gert-Joachim 1944- Hrsg (Dietz, 1991)
Rolf Reißig, Gert-Joachim Glaeßner (Herausgeber): Das Ende eines Experiments. Dietz Verlag, Berlin 1991. 357 Seiten, 29,80 DM